El rol de los padres de familia en la educación - Chusin Millingalli, Víctor Ricardo (2016)
The research is aimed to guide parents the role they should play, in the process to optimize the education of their children of the seventh year "A" from School of Basic Education "Federación Deportiva de Cotopaxi", with a negative attitude of students’parents at the time of fulfillment of their task and be responsible whit the requirements from the educational institution, a fact that undermines the emotional and intellectual aspect of most learners; problem that does not advance the expectations of educational institutions. The methodology used in the research is the literature research, interviews, surveys tabulation of results to promote the training of authorities, teachers, students and parents that participating in seminars, workshops, teamwork, this project will contribute significantly to improving the relationship family and school, also is important because helps to improve the academic level of the students and their relationship with their social environment, taking into account binding aspects, through research will focus on generating patterns that enable the implementation of a training plan for the educational community to generate ideas and strategies that improve the educational aspect benefiting directly to forty-six children and indirectly thousand fifty people involved in the instructional process, this project causes great social impact because enables the educational community involving actors in the processes of academic training who are responsible for improving, guide, direct to the educational community and especially the parents who are responsible for implementing and multiply the topic treated to reduce rates indifferent parent family with their duties, rights and the role they must meet to improving the education system in the country.